Risk Factors for Treatment Drop Out Among Pulmonary Tuberculosis Patients at the UPT Public Health Center in Medan Sunggal - Zuhair, Raisa Daffa; Ismah, Zata (International Journal of Integrated Health Sciences, 2024)
AbstractObjective: To determine the factors contributing to treatment dropout in tuberculosis (TB) patients.Methods: This study utilized a case-control design with a sample size of 81 participants. Univariate, bivariate, and multivariate analyses were conducted, and an accidental sampling technique was employed. The study was conducted at the Public Health Center/Puskesmas Medan Sunggal, in the Medan Sunggal District, City of Medan, and North Sumatra Province. The research took place from February to April 2023.Results: The research analysis revealed a significant relationship between knowledge and family support (p<0.05). However, there was no significant relationship found between drug side effects and treatment dropout (p>0.05). This lack of significance may be attributed to the consistent occurrence of side effects throughout the different stages of treatment.Conclusion: In conclusion, this research demonstrates a significant correlation between patients’ knowledge, family support, and treatment dropout (p<0.05). Conversely, no significant correlation was found between drug side effects and treatment dropout (p>0.05).Keywords: Drug side effect, pulmonary TB, TB treatment drop out